Antanas Maceina about the Essence of Upbringing and Its New Trends - Karčiauskienė, Magdalena (Acta Paedagogica Vilnensia, 1996)
A. Maceina is one of the most prominent Lithuanian philosophers of education. The article deals with outlook of A. Maceina towards the upbringing. In his publication in the journal “Židinys” (1934), A. Maceina reviewed the educational trends of that time: transcendental, psychological and vital. Vitalism, according to Maceina, mostly relies on naturalism. This direction does not take into account neither the spirit, nor God, so to Maceina it seems to be the most problematic trend. In 1935 Maceina continues the analysis of vitalism in education. He concludes that spiritual development should be in the centre of the process of upbringing. It is important in moral, as well as in physical education of children.
Keywords: History of education; philosophy of education; A. Maceina; educational trends; vitalism in education.